2022
DOI: 10.3390/jpm12050687
|View full text |Cite
|
Sign up to set email alerts
|

Endotypes of Prematurity and Phenotypes of Bronchopulmonary Dysplasia: Toward Personalized Neonatology

Abstract: Bronchopulmonary dysplasia (BPD), the chronic lung disease of prematurity, is increasingly recognized as the consequence of a pathological reparative response of the developing lung to both antenatal and postnatal injury. According to this view, the pathogenesis of BPD is multifactorial and heterogeneous with different patterns of antenatal stress (endotypes) that combine with varying postnatal insults and might distinctively damage the development of airways, lung parenchyma, interstitium, lymphatic system, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 125 publications
0
49
0
2
Order By: Relevance
“…It is located by the tracking machine following a set of guidelines; they were turned into pictures. [ 22 ], which is gradually being characterized as the result of the growing lung's defective tissue repair mechanism to both antenatal and postpartum damage. Various prenatal stressing forms interact with various prenatal impairments to produce a diverse and complex pathology, which may specifically harm the formation of the respiratory system, lung illness, cracks, and capillary systems.…”
Section: Literature Surveymentioning
confidence: 99%
“…It is located by the tracking machine following a set of guidelines; they were turned into pictures. [ 22 ], which is gradually being characterized as the result of the growing lung's defective tissue repair mechanism to both antenatal and postpartum damage. Various prenatal stressing forms interact with various prenatal impairments to produce a diverse and complex pathology, which may specifically harm the formation of the respiratory system, lung illness, cracks, and capillary systems.…”
Section: Literature Surveymentioning
confidence: 99%
“…Previous findings and our study suggest a possible role for IUI in inducing fetal and infant lung injury. BPD occurs owing to abnormal repair responses to prenatal and postnatal lung injury [ 35 ]. In this study, hematoxylin and eosin staining revealed abnormal lung morphology in neonatal mice with IUI, including fewer alveoli and simple alveolarization.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, the different endotypes of prematurity are not only the trigger for preterm birth but also induce a different pathophysiological environment for the development of fetal organs and systems. Thus, the infectious-inflammatory endotype is characterized by the development of a systemic inflammatory response with elevated cytokine levels (21, 23, 24). In turn, the placental dysfunction endotype is characterized by chronic hypoxia and imbalance of pro- and anti-angiogenic factors (21-24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preterm infants born due to HDP tend to have higher gestational ages than those born due to chorioamnionitis (22). This leads to higher clinical stability and lower incidence of respiratory complications (22, 23). Finally, exposure to HDP does not induce the inflammatory response that is induced by chorioamnionitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation